2018
DOI: 10.1186/s12890-018-0595-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pleural pressure amplitude and respiratory rate changes during therapeutic thoracentesis

Abstract: BackgroundAlthough the impact of therapeutic thoracentesis on lung function and blood gases has been evaluated in several studies, some physiological aspects of pleural fluid withdrawal remain unknown. The aim of the study was to assess the changes in pleural pressure amplitude (Pplampl) during the respiratory cycle and respiratory rate (RR) in patients undergoing pleural fluid withdrawal.MethodsThe study included 23 patients with symptomatic pleural effusion. Baseline pleural pressure curves were registered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Air mass flow was measured by Mass Flow Meter SFM3000 (Sensirion, Switzerland), while for pressure monitoring the manometer was used with a 50 Hz sampling rate, constructed by IBBE PAS (Institute of Biocybernetics and Biomedical Engineering, Polish Academy of Sciences, Warsaw, Poland). The manometer is an enhanced version of the device (IBBE PAS) dedicated to pleural pressure measurement and has been successfully used in over 60 patients up to the present [ 23 , 24 ]. The main part of the device is the Smiths Medical DPT-8003 pressure transducer, and its measuring range is equal to □+/− 300 cm H 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…Air mass flow was measured by Mass Flow Meter SFM3000 (Sensirion, Switzerland), while for pressure monitoring the manometer was used with a 50 Hz sampling rate, constructed by IBBE PAS (Institute of Biocybernetics and Biomedical Engineering, Polish Academy of Sciences, Warsaw, Poland). The manometer is an enhanced version of the device (IBBE PAS) dedicated to pleural pressure measurement and has been successfully used in over 60 patients up to the present [ 23 , 24 ]. The main part of the device is the Smiths Medical DPT-8003 pressure transducer, and its measuring range is equal to □+/− 300 cm H 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…The same group examined the change in Ppl amplitude in 23 patients, measured by the change in Ppl on inspiration and expiration, throughout thoracentesis. 49 They found that as fluid was removed there was a significant increase in median Ppl amplitude from 3.4 to 10.7 cm H 2 O. The clinical significance and physiologic basis of this finding is not immediately clear.…”
Section: Future Studies Regarding Pleural Pressurementioning
confidence: 99%
“…(Figure 2). The custombuilt system allows accurate measurements at very high frequencies which is useful when patients have high respiratory rates, which occurs towards the end of the pleural drainage (10). It can show positive and negative Ppl of each individual respiratory cycle.…”
Section: Hemodynamic Et Manometermentioning
confidence: 99%